“I want to be there for my children”: fatherhood, diabetes and temporality among Peruvian men - Pesantes, M. Amalia; Ferrazza, Isabella; Miranda, J. Jaime (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Living with a chronic condition is a challenging experience, as it can disrupt your capacity to function and fulfill social roles such as being a father. Fatherhood constitutes an important component of masculinity that has not received significant attention in studies aimed at understanding the role of gender norms in health-related behaviors. Fatherhood refers to the set of social expectations placed on men to provide, protect, and care for those considered his children. Our paper aims to show the importance of understanding men’s perspectives around fatherhood and its relevance for staying healthy. Methods In-depth semi-structured interviews with men living with Type 2 diabetes in Peru to explore their experiences with diabetes management. Results Eighteen Peruvian men, diagnosed with Type 2 diabetes for at least one year and with ages between 27 and 59 years old were interviewed. They had an average of three children each and were all insured under the national insurance plan aimed at low-income groups in Peru. Their accounts described their concern of not being able to fulfill their roles as fathers as a result of their condition. They mentioned the importance of being physically and emotionally present in the lives of their children, taking care of them, and being an example. These concerns varied depending on the age of their children: those with younger children were more preoccupied with ensuring they stayed healthy. Temporality provides a relevant analytical approach to understand the interplay of fatherhood and motivation for diabetes management. Discussion Our study advances the research around the intersection between health and gender norms and argues that a more nuanced understanding of the construction of masculinity and the relevance of fatherhood in the lives of men could be useful to design and identify better health promotion strategies tailored to men with diabetes.